A high speed 140 ghz microwave interferometer for density fluctuation measurements in Uragan-2M stellarator - Pavlichenko, R.O.; Zamanov, N.V.; Kulaga, A.E.; Uragan-2M team (Вопросы атомной науки и техники, 2018)
The operation of the 2 mm microwave superheterodyne interferometer, which allows to measure the linear electron density (average over the line of sight through the plasma) at the Uragan-2M stellarator is presented. Compared with the previously used 8 mm interferometer, this diagnostic does significantly expand the limits of the measured density of electrons which is now increased up to the value of 2.43∙10²⁰ m⁻³ . Optimized receiving and transmitting waveguide line provided a significant reduction in attenuation of the microwave radiation introduced into the plasma. It ensures that the presented experiments the value of the minimum measured density does not exceed 1.5∙10¹⁶ m⁻³. It is shown that for the different plasma discharges this system which have a high signal-tonoise ratio and high time resolution of the detector allowed to measure the “global” quasi-coherent fluctuations of the plasma density in the frequency range of 3…20 kHz.